Cytotoxicity and inhibition of nitric oxide syntheses in LPS induced macrophage by water soluble fractions of brown seaweed - Monsur, Hammed Ademola; Jaswir, Irwandi; Simsek, Senay; Amid, Azura; Alam, Md Zahangir; Tawakalit Tope, Asiyanbi-Hammed (Elsevier Inc., 2014)
A study on the anti-inflammatory role of ethanolic precipitates and supernatants of water soluble extracts of 5 brown seaweed species of Malaysian origin (Sargassum duplicatum, Sargassum binderi, Sargassum fulvellum, Padina australis and Turbinaria turbinata) on inhibition of Nitric oxide (NO) secretion in lipopolysaccharide (LPS) induced RAW264.7 murine macrophage was conducted. Results showed that fractions obtained varied in yield and chemical compositions, such as uronic acid, sulfate ion, monosaccharide, polyphenol and total sugar. In terms of yield percentage, precipitate obtained from T. turbinata contained the highest, w25%. All precipitates contained reasonable amount of fucose, mannose, galactose, glucose and xylose, but trace amount of arabinose. The precipitates inhibited NO secretion in a dose dependent manner. Precipitate of P. australis and T. turbinata, dosed at 200 mg/ml, down-regulated (more than 80%) NO secretion. Among the supernates, that of T. turbinata, which contain highest fucose, gave highest inhibition of NO synthesis. Results also showed that all the extracts obtained gave more than 80% cell proliferation except the precipitate of S. duplicatum. Data from this study also indicated that water soluble extracts of seaweed can be explored for alternative anti-inflammatory drug.